After Brexit and Other Essays. - Gamble, Andrew (Book collections on Project MUSE., 2021)
After Brexit brings together Gamble's most influential writings on British politics and political economy from the last 40 years, reflecting on issues that animate British politics, from the decline of the economy and reshaping the welfare state to the transformation of political parties and devolution to Wales, Scotland and Northern Ireland.